Composite clarifying agent for photovoltaic glass as well as preparation method and application of composite clarifying agent
By using a composite clarifier containing sodium nitrate, sodium sulfate, sodium chloride, cerium oxide and tin oxide, the problems of poor clarification and environmental pollution of traditional clarifiers are solved, and the effect of improving the quality and transparency of photovoltaic glass is achieved, while reducing the use of harmful substances.
Patent Information
- Application Number
- CN202411877829.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional clarifiers for photovoltaic glass have limited clarification effects and are unfriendly to the environment, making it difficult to meet the demand for high-quality glass in modern glass production.
A composite clarification agent is used, including 10-20% sodium nitrate, 15-25% sodium sulfate, 10-20% sodium chloride, 15-22% cerium oxide and 25-35% tin oxide. Through the interaction of these components, the bubbles in the glass liquid are discharged and the quality and transparency of the glass are improved.
This composite clarifier can effectively reduce the content of bubbles in the glass, improve the transparency and quality of the glass. At the same time, since it does not contain toxic and harmful elements such as As and Sb, it reduces the pollution impact on operators and the environment.
Smart Images

Figure BDA0005197382930000091 
Figure BDA0005197382930000101 
Figure BDA0005197382930000102
Abstract
Description
Technical Field
[0001] The invention relates to a composite clarifier for photovoltaic glass and a preparation method and application thereof, belonging to the technical field of photovoltaic glass. Background Art
[0002] Photovoltaic glass is a special glass that can generate electricity using solar radiation by laminating solar cells and has related current extraction devices and cables. It is mainly composed of glass, solar cells, film, back glass, special metal wires, etc. It is a novel high-tech glass product for construction.
[0003] Photovoltaic glass has the following characteristics and advantages:
[0004] High light transmittance: Low iron glass is used to cover the solar cell to ensure more light transmittance, so that the solar cell can generate more electricity. For example, the current mainstream low iron tempered embossed glass has a light transmittance of more than 91% within the wavelength range of the solar cell spectrum response (380-1100nm).
[0005] High strength: Tempered low-iron glass has higher strength and can withstand greater wind pressure and larger temperature differences between day and night.
[0006] Good weather resistance: It can work stably for a long time under various harsh climatic conditions, and has good high temperature resistance, oxidation resistance, corrosion resistance and other properties to ensure the service life of photovoltaic modules.
[0007] Aesthetics: It can be applied to building curtain walls, photovoltaic roofs, etc. It has a certain aesthetics and realizes the integration of buildings and photovoltaic power generation.
[0008] The production of photovoltaic glass is to mix the raw materials in a certain proportion and melt them into glass liquid at high temperature. Then, through processes such as calendering and annealing, the glass liquid is formed into a raw sheet with a specific thickness and shape. Finally, the raw sheet is cut and inspected to obtain a photovoltaic glass raw sheet that meets the requirements.
[0009] In the glass manufacturing process, clarification is a key link, the purpose of which is to remove bubbles in the glass liquid to improve the quality and transparency of the glass. Traditional clarifiers usually use a single component, such as arsenic, antimony oxide, etc., but these single clarifiers have some problems, such as limited clarification effect and unfriendly to the environment. Therefore, the development of an efficient and environmentally friendly composite clarifier has become an urgent need in the field of glass manufacturing. Summary of the invention
[0010] In view of this, the present invention provides a composite clarifier for photovoltaic glass and a preparation method and application thereof. The technical problem to be solved is how to improve a composite clarifier that can promote the discharge of bubbles in the glass liquid and improve the quality and transparency of the glass.
[0011] The purpose of the present invention and the technical problem solved are achieved by the following technical measures: The present invention proposes a composite clarifier for photovoltaic glass production, which comprises, by weight percentage: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide.
[0012] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0013] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 13-17% sodium nitrate; 17-23% sodium sulfate; 14-17% sodium chloride; 18-22% cerium oxide; and 27-32% tin oxide.
[0014] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 16% sodium nitrate; 18% sodium sulfate; 17% sodium chloride; 18% cerium oxide; and 31% tin oxide.
[0015] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 17% sodium nitrate; 21% sodium sulfate; 16% sodium chloride; 16% cerium oxide; and 30% tin oxide.
[0016] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 15% sodium nitrate; 20% sodium sulfate; 15% sodium chloride; 20% cerium oxide; and 30% tin oxide.
[0017] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 16% sodium nitrate; 19% sodium sulfate; 14% sodium chloride; 22% cerium oxide; and 29% tin oxide.
[0018] Preferably, the aforementioned composite clarifier for photovoltaic glass production, wherein the composite clarifier comprises, by weight percentage: 13% sodium nitrate; 22% sodium sulfate; 18% sodium chloride; 18% cerium oxide; and 29% tin oxide.
[0019] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a method for preparing a composite clarifier for photovoltaic glass production, comprising the following steps: uniformly mixing 10-20% sodium nitrate, 15-25% sodium sulfate, 10-20% sodium chloride, 15-22% cerium oxide and 25-35% tin oxide by weight percentage to obtain the composite clarifier for photovoltaic glass production.
[0020] The purpose of the present invention and the technical problem solved by the present invention are achieved by adopting the following technical solutions. The present invention proposes a glass batch material, which includes 0.4%-1.3% of a composite clarifier by weight; the composite clarifier includes: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide by weight.
[0021] The purpose of the present invention and the solution of its technical problems can also be achieved by the following technical measures. The present invention proposes an application of a composite clarifier in the production of photovoltaic glass; the composite clarifier comprises, by weight percentage: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide.
[0022] Compared with the prior art, the composite clarifier for photovoltaic glass of the present invention and its preparation method and application have the following beneficial effects:
[0023] The composite clarifier for photovoltaic glass production of the present invention does not contain toxic and harmful elements such as As and Sb, which effectively reduces the adverse effects of the operation process on the health of operators and also reduces the harmful effects on the environment during the production process;
[0024] The composite clarifier for photovoltaic glass production of the present invention can promote the discharge of bubbles in the glass liquid and improve the quality and transparency of the glass.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0026] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a composite clarifier for photovoltaic glass and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0027] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0028] In the glass production process, clarifiers play a vital role. They can promote the discharge of bubbles in the glass liquid and improve the quality and transparency of the glass. However, traditional clarifiers often have some problems. On the one hand, many traditional clarifiers such as arsenic and antimony oxides are not environmentally friendly and will cause environmental pollution during production and use. On the other hand, the clarification effect of these traditional clarifiers is limited and it is difficult to meet the demand for high-quality glass in modern glass production.
[0029] To this end, some embodiments of the present invention provide a composite clarifier for photovoltaic glass production, which comprises, by weight percentage: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; 25-35% tin oxide, so as to solve the problem that traditional clarifiers are not environmentally friendly and have poor clarification effects.
[0030] In some embodiments, optionally, the composite clarifier comprises, by weight percentage: 13-17% sodium nitrate; 17-23% sodium sulfate; 14-17% sodium chloride; 18-22% cerium oxide; and 27-32% tin oxide.
[0031] In the above technical solution, the content and function of each component are analyzed as follows:
[0032] Sodium nitrate: This substance can decompose and produce gas at high temperature, thus promoting the discharge of bubbles in the glass liquid. At the same time, it has good environmental performance and will not pollute the environment. Sodium nitrate has strong oxidizing properties. During the glass melting process, it can react with other substances to react with oxidation to promote the removal of bubbles in the glass liquid. When heated to a certain temperature (about 380°C), it will decompose and produce gases such as oxygen. The production of these gases helps to increase the volume of bubbles in the glass liquid, accelerate their rise and discharge, and thus achieve the effect of clarification. Under high temperature conditions of glass melting, sodium nitrate decomposes to produce gases such as oxygen. These gases enter the bubbles in the glass liquid, reduce the partial pressure of the gas in the bubbles, and make the bubbles grow more easily. At the same time, the oxidation of sodium nitrate can change the state or properties of certain substances in the glass liquid, making it more conducive to the removal of bubbles. For example, some tiny bubbles that were originally difficult to discharge may become easier to be absorbed by the glass liquid or merged into larger bubbles for discharge. However, excessive use may cause excessive nitrate ions to remain in the glass liquid, which may have a certain impact on the performance of the glass, such as the chemical stability of the glass. According to actual research results, the sodium nitrate content is 10-20wt%, and the preferred content is 13-17wt%. The preferred sodium nitrate content can ensure that the bubble content in the glass is effectively reduced while minimizing the negative impact on the chemical stability and optical properties of the glass.
[0033] Sodium sulfate: Sodium sulfate decomposes at high temperatures. Generally, at glass melting temperatures (usually above 1500°C), sodium sulfate decomposes into sodium oxide (Na2O) and sulfur dioxide (SO2) gas. This decomposition characteristic enables sodium sulfate to produce gas during the glass melting process, thereby providing power for the clarification process. The sulfur dioxide gas produced has strong diffusivity and permeability, and can quickly enter the bubbles in the glass liquid, reduce the pressure inside the bubbles, and cause the bubbles to grow and rise to discharge from the glass liquid. The clarification effect of sodium sulfate is more significant, and it can effectively remove tiny bubbles in the glass liquid and improve the quality and transparency of the glass. After the sulfur dioxide gas produced by the decomposition of sodium sulfate enters the bubbles in the glass liquid, according to the ideal gas law, the total pressure in the bubbles is equal to the sum of the partial pressures of the gases of each component. The addition of sulfur dioxide reduces the partial pressure of the original gas in the bubbles, increasing the volume of the bubbles. As the volume of the bubbles increases, their buoyancy also increases accordingly, thereby accelerating the rising speed of the bubbles in the glass liquid, making it easier to discharge from the surface of the glass liquid. In the glass melting process, sodium sulfate can also participate in redox reactions. It can react with certain reducing substances in the glass liquid and oxidize them into substances with higher valence states. For example, sodium sulfate can react with reducing substances such as carbon to generate carbon dioxide gas. These additionally generated gases also help promote the discharge of bubbles and improve the clarification effect. The presence of sodium sulfate can also affect the surface tension of the glass liquid. Appropriate surface tension can make the bubbles in the glass liquid easier to gather and merge, forming larger bubbles, which are easier to discharge. The amount of sodium sulfate needs to be reasonably adjusted according to the specific glass formula and production process. If the amount is too much, it may cause too much sulfate to remain in the glass liquid, affecting the chemical stability and other properties of the glass. If the amount is too little, a good clarification effect may not be achieved. Therefore, when using sodium sulfate as a clarifier, strict testing and optimization are required to determine the optimal dosage range. According to the actual research results, the sodium sulfate content is 15-25wt%, and the preferred content is 17-23wt%. The preferred sodium sulfate content can minimize the negative impact on the chemical stability and optical properties of the glass while ensuring the effective reduction of the bubble content in the glass.
[0034] Sodium chloride: Sodium chloride can reduce the viscosity of glass liquid during the glass melting process. The lower viscosity makes it easier for bubbles in the glass liquid to rise and discharge, thereby improving the clarification effect. This is because sodium chloride can change the structure of the glass liquid, weaken the interaction between glass molecules, and enhance fluidity. Sodium chloride is a relatively stable compound that is not easy to decompose or react violently with other substances during the glass melting process. This allows it to maintain a stable clarification effect over a wide temperature range and will not affect the quality of the glass due to temperature changes. Sodium chloride is a common chemical with a wide source and a relatively low price. Using sodium chloride as a clarifier can reduce the cost of glass production and improve economic benefits. Sodium chloride can interact with other components in the glass liquid to adjust the chemical composition of the glass. For example, it can react with substances such as silicon oxide to produce compounds such as sodium silicate, thereby changing the physical and chemical properties of the glass. This regulatory effect can affect the clarification effect, hardness, heat resistance and other properties of the glass. Therefore, when using sodium chloride as a clarifier, it is necessary to make reasonable adjustments based on the specific glass formula and performance requirements. The amount of sodium chloride needs to be reasonably controlled according to the type, formula and production process of the glass. If the dosage is too much, the residual sodium chloride in the glass liquid may be too high, affecting the chemical stability and optical properties of the glass. If the dosage is too little, a good clarification effect may not be achieved. Therefore, when using sodium chloride as a clarifier, it is necessary to test and optimize to determine the best dosage range. According to actual research results, the sodium chloride content is 10-20wt%, and the preferred content is 14-17wt%. The preferred sodium chloride content can ensure that the bubble content in the glass is effectively reduced while minimizing the negative impact on the chemical stability and optical properties of the glass.
[0035] Cerium oxide: Cerium oxide has strong oxidizing properties. During the glass melting process, it can react with reducing substances in the glass liquid to release oxygen. These oxygen can enter the bubbles in the glass liquid, reduce the partial pressure of the gas in the bubbles, and cause the bubbles to grow and rise and discharge, thereby clarifying the glass liquid. Cerium oxide has good stability at high temperatures and is not easy to decompose or volatilize. This enables it to continue to play a clarifying role in the high-temperature environment of glass melting and will not lose its effect due to temperature changes. Cerium oxide has high chemical stability and is not easy to react with other components in the glass liquid, and will not have an adverse effect on the chemical composition and properties of the glass. Compared with some traditional clarifiers, cerium oxide is relatively environmentally friendly. It does not contain substances that are harmful to the environment, such as arsenic and antimony, and meets the environmental protection requirements of modern glass production. In addition to the clarification effect, cerium oxide can also improve the quality of glass. It can improve the refractive index, hardness and chemical stability of glass, making the glass more durable and beautiful. The amount of cerium oxide needs to be reasonably controlled according to the type, formula and production process of glass. If the dosage is too much, the residual cerium oxide in the glass liquid may be too high, affecting the optical properties and chemical stability of the glass. If the dosage is too little, a good clarification effect may not be achieved. Therefore, when using cerium oxide as a clarifier, it is necessary to test and optimize to determine the best dosage range. According to the actual research results, the cerium oxide content is 15-22wt%, and the preferred content is 18-22wt%. The preferred cerium oxide content can ensure that the bubble content in the glass is effectively reduced while minimizing the negative impact on the chemical stability and optical properties of the glass.
[0036] Tin oxide: Tin oxide can decompose at high temperatures to produce oxygen, which can enter the bubbles in the glass liquid, reduce the pressure inside the bubbles, and cause the bubbles to grow and rise and discharge, thereby effectively improving the clarity of the glass. Compared with other clarifiers, tin oxide has a more significant clarification effect, can handle tiny bubbles in the glass liquid, and make the glass more transparent. Tin oxide has high chemical stability, is not easy to react with other substances during the glass melting process, and will not have adverse effects on the chemical composition and properties of the glass. This allows tin oxide to be used in various glass formulations and has a wide range of applicability. Tin oxide does not contain substances that are harmful to the environment, such as arsenic, antimony and other components in traditional clarifiers. Using tin oxide as a clarifier can reduce the pollution of glass production to the environment and meet modern environmental protection requirements. Unlike some clarifiers, tin oxide has little effect on the color of the glass during use. It will not cause obvious changes in the color of the glass and can maintain the original color of the glass. The amount of tin oxide needs to be reasonably adjusted according to the type, formula and production process of the glass. If the amount is too much, the residual tin oxide in the glass liquid may be too high, affecting the performance of the glass. If the amount is too little, a good clarification effect may not be achieved. Therefore, when using tin oxide as a clarifier, it is necessary to conduct tests and optimization to determine the best dosage range. According to actual research results, the tin oxide content is 25-35wt%, and the preferred content is 27-32wt%. The preferred tin oxide content can ensure that the bubble content in the glass is effectively reduced while minimizing the negative impact on the chemical stability, crystallization characteristics and optical properties of the glass.
[0037] In some optional embodiments, the composite clarifier comprises, by weight percentage: 16% sodium nitrate; 18% sodium sulfate; 17% sodium chloride; 18% cerium oxide; and 31% tin oxide.
[0038] In some optional embodiments, the composite clarifier comprises, by weight percentage: 17% sodium nitrate; 21% sodium sulfate; 16% sodium chloride; 16% cerium oxide; and 30% tin oxide.
[0039] In some optional embodiments, the composite clarifier comprises, by weight percentage: 15% sodium nitrate; 20% sodium sulfate; 15% sodium chloride; 20% cerium oxide; and 30% tin oxide.
[0040] In some optional embodiments, the composite clarifier comprises, by weight percentage: 16% sodium nitrate; 19% sodium sulfate; 14% sodium chloride; 22% cerium oxide; and 29% tin oxide.
[0041] In some optional embodiments, the composite clarifier comprises, by weight percentage: 13% sodium nitrate; 22% sodium sulfate; 18% sodium chloride; 18% cerium oxide; and 29% tin oxide.
[0042] Some embodiments of the present invention also provide a method for preparing a composite clarifier for photovoltaic glass production, comprising the following steps: uniformly mixing 10-20% sodium nitrate, 15-25% sodium sulfate, 10-20% sodium chloride, 15-22% cerium oxide and 25-35% tin oxide by weight percentage to obtain the composite clarifier for photovoltaic glass production.
[0043] Furthermore, the preparation method specifically comprises the following steps:
[0044] A weighs the corresponding raw materials by weight percentage: 10-20% sodium nitrate, 15-25% sodium sulfate, 10-20% sodium chloride, 15-22% cerium oxide and 25-35% tin oxide;
[0045] B puts the weighed raw materials into a mixer for mixing;
[0046] C transfers the evenly mixed clarifier into the silo container for batching.
[0047] Some embodiments of the present invention further provide a glass batch material, which includes 0.4%-1.3% of a composite clarifier by weight. An appropriate amount of clarifier can effectively improve the clarification effect of the glass liquid and reduce the number of bubble defects in the glass product. When the amount is less than 0.4%, the clarification effect cannot meet the requirements. When the amount of clarifier is more than 1.3%, the glass transmittance decreases and causes the occurrence of glass crystallization defects.
[0048] Some embodiments of the present invention also provide an application of a composite clarifier in the production of photovoltaic glass. The composite clarifier is mainly used to reduce the number of bubble defects in glass products and improve the yield rate, but cannot change the transmittance of the glass.
[0049] When the present invention is implemented, the required amounts of various raw materials are first calculated according to the designed glass components, and then various raw materials are weighed according to the calculated results. After stirring and mixing them evenly, the mixed raw materials are poured into a glass test furnace and melted according to a certain temperature system. After the melting is completed, the glass liquid is poured into a mold for cooling and forming into a glass ingot with a regular shape. Then, a strong light flashlight is used to observe the number of bubbles in the glass ingot. The total number of bubbles is compared with the weight of the glass ingot to obtain the number of bubbles per kilogram of glass. The data can reflect the clarification effect of the glass.
[0050] The present invention is further described below in conjunction with specific embodiments.
[0051] In the embodiments and comparative examples in Table 1, Table 2 and Table 3, the glass samples were all prepared by the following method:
[0052] Calculate the amount of various raw materials required based on the output of 1500g of glass;
[0053] Weigh various raw materials in sequence and put them into a mixer to stir and mix them evenly;
[0054] Transfer the mixed material into a platinum crucible and place the crucible into a high-temperature test furnace;
[0055] The melting furnace control temperature was set to 1620°C and the melting time was 10 hours;
[0056] After melting, pour the glass liquid in the crucible into a cast iron mold preheated at 310°C and naturally cold-form (cool to room temperature). The size of the formed glass ingot is 140*200*20mm. Weigh the weight of the glass ingot (kg);
[0057] Use a strong flashlight to illuminate the side of the glass, observe and record the number of bubbles with the naked eye, and calculate the number of bubbles per kg of the glass ingot.
[0058] Example 1-1 to Example 1-5
[0059] Weigh 1070 g of quartz sand, 14 g of aluminum oxide, 335 g of sodium carbonate, 60 g of magnesium oxide, 283 g of calcium carbonate, and 14.2 g of a composite clarifier, wherein the composite clarifier accounts for 0.8% of the total amount of the batch; mix the above various raw materials evenly and then melt them at a high temperature (1620° C., 10 hours). The number of bubbles per kg of the obtained glass ingot is shown in Table 1 below.
[0060] Table 1
[0061]
[0062] Example 2-1 to Example 2-5
[0063] Weigh 1070 g of quartz sand, 14 g of aluminum oxide, 335 g of sodium carbonate, 60 g of magnesium oxide, 283 g of calcium carbonate, and 10.7 g of a composite clarifier, wherein the composite clarifier accounts for 0.6% of the total amount of the batch; mix the above various raw materials evenly and then melt them at a high temperature (1620° C., 10 hours). The number of bubbles per kg of the obtained glass ingot is shown in Table 2 below.
[0064] Table 2
[0065]
[0066] Comparative Example 1-1 to Comparative Example 1-5
[0067] Weigh 1070 g of quartz sand, 14 g of aluminum oxide, 335 g of sodium carbonate, 60 g of magnesium oxide, 283 g of calcium carbonate, and 14.2 g of a composite clarifier, wherein the composite clarifier accounts for 0.8% of the total amount of the batch; mix the above various raw materials evenly and then melt them at a high temperature (1620° C., 10 hours). The number of bubbles per kg of the obtained glass ingot is shown in Table 3 below.
[0068] Table 3
[0069]
[0070] From the data in Tables 1-3, it can be seen that the bubble content of the glass melted according to the ratio in the example is significantly lower than that of the glass in the comparative example, which indicates that the composite clarifier according to the ratio of the present invention has a better clarification effect.
[0071] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0072] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0073] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0074] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A composite clarifier for photovoltaic glass production, characterized in that: Calculated by weight percentage, it comprises: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide.
2. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 13-17% sodium nitrate; 17-23% sodium sulfate; 14-17% sodium chloride; 18-22% cerium oxide; and 27-32% tin oxide.
3. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 16% sodium nitrate; 18% sodium sulfate; 17% sodium chloride; 18% cerium oxide; and 31% tin oxide.
4. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 17% sodium nitrate; 21% sodium sulfate; 16% sodium chloride; 16% cerium oxide; and 30% tin oxide.
5. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 15% sodium nitrate; 20% sodium sulfate; 15% sodium chloride; 20% cerium oxide; and 30% tin oxide.
6. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 16% sodium nitrate; 19% sodium sulfate; 14% sodium chloride; 22% cerium oxide; and 29% tin oxide.
7. The composite clarifier for photovoltaic glass production according to claim 1, characterized in that: The composite clarifier comprises, by weight percentage: 13% sodium nitrate; 22% sodium sulfate; 18% sodium chloride; 18% cerium oxide; and 29% tin oxide.
8. A method for preparing a composite clarifier for photovoltaic glass production, characterized in that: The following steps are involved: 10-20% of sodium nitrate, 15-25% of sodium sulfate, 10-20% of sodium chloride, 15-22% of cerium oxide and 25-35% of tin oxide are uniformly mixed by weight percentage to obtain the composite clarifier for photovoltaic glass production.
9. A glass batch material, comprising 0.4%-1.3% of a composite clarifier by weight; the composite clarifier comprises: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide by weight.
10. Application of a composite clarifier in photovoltaic glass production, characterized in that: The composite clarifier comprises, by weight percentage: 10-20% sodium nitrate; 15-25% sodium sulfate; 10-20% sodium chloride; 15-22% cerium oxide; and 25-35% tin oxide.
Citation Information
Patent Citations
Glass clarifier and glass preparation method
CN105084756A
Compound clarifying agent for light guide plate glass produced through float glass process
CN107445471A
Compound clarifying agent for high aluminosilicate glass
CN109133612A
Alkali-free aluminosilicate glass clarifying agent and preparation method of glass
CN113173702A
Melting and clarifying method of medium borosilicate medicinal glass
CN114394730A
Cited By
A composite clarifying agent, its preparation method and application
CN122562324A